The Role of Constitution in a Democratic System and Human Rights Protection in Indonesia - Firmansyah, Firmansyah; Budiyono, Budiyono (Pancasila and Law Review, 2024)
The constitution is the legal foundation of a country, which includes the protection of human rights and the regulation of the division of power in running the country's government. The Indonesian Constitution has specific purposes and functions in ensuring democracy and human rights. As a legal instrument of democracy, the Constitution is important in a country's legal system. General elections are an important moment in realizing the sovereignty of citizens. The Indonesian system of government, as stipulated in the 1945 Constitution and its explanations, is a democracy, both in direct and representative forms. The Constitution guarantees the rights of the people, including the rights to assembly, association and expression. The right to life is considered a basic right that must be respected and upheld according to the Indonesian constitution.